Le néofantastique : un jeu avec le fantastique traditionnel ? - Gadomska, Katarzyna (Romanica Silesiana)
The traditional fantastic literature of the nineteenth century is a genre par excellence codificated. The present study indicates how the new fantastic literature of the twentieth and the twenty-first century plays with these codes and with the customs of the traditional reader. This work discusses the literary games, very diversified, on the level of the content (the modifications of the traditional fantastic motives, for example the motif of a ghost or of a vampire) and on the level of the form (the new techniques of writing versus the traditional techniques of the literature referring to the supernatural). The present study analyses the short stories by writers writing in French, for example Rémi Karnauch, Jean-Pierre Andrevon, Stéphanie Benson, Pierre Pelot, Yves and Ada Rémy, and Jean-Pierre Bours. Key worda: Tale of twilight, the supernatural, horror, fear, ghost, vampire, game.